2005
DOI: 10.1051/parasite/2005124317
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting helminths community structure of the Egyptian lizardChalcides ocellatus(Forskal, 1775)

Abstract: Summary :The variation in the component community structure of intestinal helminths in the lizard Chalcides ocellatus (Forskal, 1775) was studied in relation to the seasonal variation and host weight and sex. 120 lizards were collected seasonally during year 2004, from Al Firdan, Ismailia governorate, Egypt. The helminths community consisted of six species (five nematodes and one cestode). The various helminths differed according to host sex. The prevalence of total helminths infection was 67.6 % while the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Other reports: Morocco cylindrical skink, Chalcides mionection (Baker, 1987); Chalcides ocellatus (Moravec et al, 1987;Elwasila, 1990;Ashour et al, 1994;Al-Deen et al, 1995;Ibrahim and Soliman, 2005); La. stellio (Ghobashy, 2006); Aegean wall lizard, Podarcis erhardii (Roca et al, 2009); Po.…”
Section: Site Of Infection: Small Intestinementioning
confidence: 95%
See 1 more Smart Citation
“…Other reports: Morocco cylindrical skink, Chalcides mionection (Baker, 1987); Chalcides ocellatus (Moravec et al, 1987;Elwasila, 1990;Ashour et al, 1994;Al-Deen et al, 1995;Ibrahim and Soliman, 2005); La. stellio (Ghobashy, 2006); Aegean wall lizard, Podarcis erhardii (Roca et al, 2009); Po.…”
Section: Site Of Infection: Small Intestinementioning
confidence: 95%
“…Although reports of helminths from C. ocellatus are available (Parona, 1887(Parona, , 1900Lühe, 1898;Barbagallo, 1901;Mingazzini, 1904;Seurat, 1917;Joyeux, 1923;Della Santa, 1956;Belle, 1957;Moravec et al, 1987;Elwasila, 1990;Ashour et al, 1992Ashour et al, , 1994Al-Deen et al, 1995;Al-Deen and Al-Shareef, 1996;Ibrahim and Soliman, 2005;Cano et al, 2006;Schuster, 2011), this is, to our knowledge, the first report of helminths from C. ocellatus collected in Turkey.…”
mentioning
confidence: 95%
“…The relationship between the host sex and occurrence of intestinal nematodes of the Egyptian lizard was described as a debate issue (Ibrahim & Soliman 2005). In this study, difference between total prevalence of infection in male and female lizards was small while the intensity of infection was the highest in female lizards in the studied seasons.…”
Section: Discussionmentioning
confidence: 55%
“…The variation in the structure of intestinal helminths community of the Egyptian lizard, C. ocellatus (One of the most abundant and widespread reptile species in Africa and Egypt) in relation to seasonal variation , host weight and sex was previously studied (Ibrahim & Soliman 2005). Unfortunately, the possible affect of the host reproductive cycle on the dynamics of infection with such community was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding general patterns of animal communities is one of the main aims in ecological research (Morton et al , 1996). At the parasitological level, it has been observed that the helminth community in the same host population can vary seasonally, resulting in diversity changes (Boggs et al , 1990; Ibrahim & Soliman, 2005). These seasonal changes may occur due to extrinsic factors (environmental factors) that affect the survival of free-living parasitic stages, or the density, diet or susceptibility of both intermediate and definitive hosts (Healey & Grundmann, 1974; Roepstorff & Murrell, 1997; Torres et al , 2006; Cornell et al , 2008).…”
Section: Introductionmentioning
confidence: 99%